Role of ABO Blood Group in SARS-CoV-2 Infection in Households - Janda, Ales; Engel, Corinna; Remppis, Jonathan; Enkel, Sigrid; Peter, Andreas; Hörber, Sebastian; Ganzenmueller, Tina; Schober, Sarah; Weinstock, Christof; Jacobsen, Eva-Maria; Fabricius, Dorit; Zernickel, Maria; et al. (Frontiers in Microbiology, 2022)
An association between certain ABO/Rh blood groups and susceptibility to SARS-CoV-2 infection has been proposed for adults, although this remains controversial. In children and adolescents, the relationship is unclear due to a lack of robust data. Here, we investigated the association of ABO/Rh blood groups and SARS-CoV-2 in a multi-center study comprising 163 households with 281 children and 355 adults and at least one SARS-CoV-2 seropositive individual as determined by three independent assays as a proxy for previous infection. In line with previous findings, we found a higher frequency of blood group A (+6%) and a lower frequency of blood group O (-6%) among the SARS-CoV-2 seropositive adults compared to the seronegative ones. This trend was not seen in children. In contrast, SARS-CoV-2 seropositive children had a significantly lower frequency of Rh-positive blood groups. ABO-compatibility did not seem to play a role for SARS-CoV-2 transmission within the families. A correction for family clusters was performed and estimated fixed effects of the blood group on the risk of SARS-CoV-2 seropositivity and symptomatic infection were determined. Although we found a different distribution of blood groups in seropositive individuals compared to the reference population, the risk of SARS-CoV-2 seropositivity or symptomatic infection was not increased in children or in adults with blood group A or AB versus O or B. Increasing age was the only parameter positively correlating with the risk of SARS-CoV-2 infection. In conclusion, specific ABO/Rh blood groups and ABO-compatibility appear not to predispose for SARS-CoV-2 susceptibility in children.